Migration Response of Astrocytes to the Effect of Conditioned Medium From Rat Bone Marrow Mesenchymal Stem Cells - Székiová, Eva; Michalová, Zuzana; Blaško, Juraj; Vanický, Ivo (Problems of Cryobiology and Cryomedicine, 2024)
Probl Cryobiol Cryomed 2024; 34(4):304